Retraction: Adyel et al. Health Risk Assessment of Pesticide Residues via Dietary Intake of Market Vegetables from Dhaka, Bangladesh. Foods 2013, 2, 64–75 - Md. Shakhaoat Hossain; Md. Alamgir Hossain; Md. Abdur Rahman; Md. Mainul Islam; Md. Atiqur Rahman; Tanveer Mehedi Adyel (Foods, 2013)
The following article [1], doi: 10.3390/foods2010064, website: http://www.mdpi.com/2304-8158/2/1/64, has been retracted by the authors because of some major errors in broad field of pesticide residues identification and concentrations. During random cross check retention time of pesticides by HPLC did not match with the standards of detected pesticides. As a result concentration of all detected pesticides, maximum residue limits (MRLs) and health risk assessments were changed. All these errors made the article [1] as a wrong one. All authors have confirmed that the reported results produced using quite inappropriate procedures. As first author herein, I take full responsibility for the retraction of our experiments and any other errors in its contents, and would like to offer my apologies on behalf of my co-authors to the readership of Foods for any inconveniences caused by this retraction.